The Safety and Efficacy Evaluation of PRRS Attenuated Vaccine BG895 Strain in Experimental Pigs - Thy, Bui Anh; Truong, Nguyen Tang; Phuc, Kim Van; Thu, Nguyen Thien; Dung, Nguyen Van; Hanh, Tran Xuan; Thuoc, Tran Linh (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 1, 2022)
From the PRRSV virulent strain BG8 isolated from a PRRSV-infected pig, using serial passage method in MARC-145 cell line, we have successfully obtained an attenuated strain in 95 th passage, named as BG895, with high potential to be a vaccine candidate. In this study, we present the results of the safety and efficacy evaluation of BG895 against PRRSV in experimental pigs. Trial results of vaccine formula using strain BG895 have very high safety when inoculating 5 doses/animal and 10 doses/animal. Evaluation of immune response by ELISA method showed that, from 14 days post inoculation, anti-PRRSV antibodies were detected in the serum of all inoculated pigs in vaccine batches with the lowest S/P index of 1.50 ± 0.4 and the highest S/P was 2.36 ± 0.1 from 28 days post inoculation. The IPMA method showed that the antibody titer of the vaccine reached ≥ 1/160 in 100% of pigs from 21 days post inoculation andreached ≥ 1/640 in 100% of pigs from 28 days post inoculation, indicating that the vaccine was effective at protecting 100% of pigs from 28 days post inoculation. The protective effect of the vaccine was evaluated by the virulent challenge from 28 days post inoculation with 1 dose/animal compared with the control group. The results showed that compared with all pigs in the control group with typical clinical manifestations of Blue-ear disease, all inoculated pigs had normal body temperature and weight gain, besides, the S/P index increased from 1.65 ± 0.1 to the highest 2.99 ± 0.2; the average antibody titer was >1/2560, and virus wasnot detected in nasal fluid by real-time RT-PCR from 7 days post challenge. These experimental results confirmed the safety and efficacy of the attenuated PRRS vaccine based on BG895strain.